Acetabular fractures treatment needs in the elderly and nonagenarians. Issue 6 (31st May 2022) - Riemenschneider, Julia; Vollrath, Jan Tilmann; Mühlenfeld, Nils; Frank, Johannes; Marzi, Ingo; Janko, Maren
Abstract : Different treatment options for acetabular fractures in the elderly and nonagenarians exist; a consistent guideline has not been established, yet. The purpose of this study is to give an overview of how those fractures can be handled and compares two different surgical treatment methods. A total of 89 patients ≥ 18 years between 2016 and 2021 with acetabular fractures in our department received a surgical intervention with plate fixation via the Stoppa approach or a total hip arthroplasty with a Burch–Schneider ring and integrated cup. 60 patients ≥ 65 were compared in two groups, 29 patients between 65 and 79 and 31 patients ≥ 80. For comparison, data on operation times, hospitalization, complications during operation and hospital stay, blood loss and postoperative mobilization were collected. Characteristics could be found for indications for operative osteosynthesis or endoprosthetics based on the X-ray analysis. There was a tendency to treat simple fractures with osteosynthesis. Patients between 65 and 79 with an osteosynthesis had benefits in almost every comparison. Patients ≥ 80 with a plate fixation had advantages in the categories of postoperative complications, blood loss and transfusion of erythrocyte concentrates. Statistical significant differences were noticed in both groups regarding the operation time. Patients between 65 and 79 with osteosynthesis had significant benefits for postoperative complications, hospitalization, number of blood transfusions and postoperative mobilization. Finding the best supportive treatment option is difficult, and decision-making must respect fracture patterns and individual risk factors. This study shows that plate fixation via the Stoppa approach has some benefits.